Maritime Security in the Indian Ocean: The Region-Centric Multilateral Approach - Mr. Sohail Ahmad Azmie (CISS Insight Journal, 2017)
Indian Ocean is one of the most talked about oceans in the world today. Its significance is multidimensional: it has the most conflicts in its region and is the busiest conduit of world trade. It has also been the focus of super power rivalry during the Cold War and is gaining renewed attention in recent times as the geostrategic interests of the major world powers re-converge in its waters. With the rising politico-strategic foci on its shores, there is increasing evidence of maritime crime in the Indian Ocean, of late. Though substantially abated, yet piracy in the Horn of Africa and Gulf of Aden coupled with maritime terrorism, drug trafficking and human smuggling are the signs of some serious disturbances to peace and stability in the Ocean, demanding a credible maritime response. The vastness of the Ocean makes it virtually impossible for a single littoral nation to remain successful against these challenges. The changing threat mosaic necessitates a relook at the models of fighting, the threats and the prevailing situation in a diminished maritime security milieu. A paradigm shift from ‘confrontational’ to ‘cooperative’ approach is essential; whereby regional littorals may come together to operate their maritime forces for better preservation of their maritime interests whilst not allowing the extra-regional actors to interfere with the regional settings. This new method may be termed as ‘regioncentric multilateral approach’.